Gambaran histologi ovarium sapi aceh pascavitrifikasi menggunakan dimetyl sulfoksida dengan konsentrasi berbeda - . Syafruddin; Arman Sayuti; Rahmat Aditya Sumardi; Budianto Panjaitan (ARSHI Veterinary Letters, 2018)
This study aims to determine the morphology of Aceh bovine ovarian pasca vitrification, after its been exposed to dimetyl sulfoksida (DMSO) cryoprotectant. This study use a completely randomized design of one-way pattern ANOVA acquire three replications. Ovaries used in this study are Aceh cattle ovarian which collected from slaughter house (RPH) accounted as 4 organs, to the next sliced into 9 pieces. Ovarian pieces are then grouped into 3 treatment groups namely ovaries which exposed into solution containing DMSO 10% (P1), 20% (P2), and 30% (P3). The results showed that the average number of normal follicles is highest at P1 41,33 ± 32,51; followed by P2 20,00 ± 16,09 , and P3 15,66 ± 10,50. It was concluded that  the ovarian tissue was exposed with DMSO 10% was able to maintain of the normal follicle than DMSO 20% and 30% although statistical test results showed no significant difference between group (P>0,05).